An Intragenic Recombination Event Generates a Snf4-Independent Form of the Essential Protein Kinase Snf1 in Candida albicans - Austin Mottola (American Society for Microbiology, 2019)
ABSTRACT The heterotrimeric protein kinase SNF1 plays a key role in the metabolic adaptation of the pathogenic yeast Candida albicans. It consists of the essential catalytic α-subunit Snf1, the γ-subunit Snf4, and one of the two β-subunits Kis1 and Kis2. Snf4 is required to release the N-terminal catalytic domain of Snf1 from autoinhibition by the C-terminal regulatory domain, and snf4Δ mutants cannot grow on carbon sources other than glucose. In a screen for suppressor mutations that restore growth of a snf4Δ mutant on alternative carbon sources, we isolated a mutant in which six amino acids between the N-terminal kinase domain and the C-terminal regulatory domain of Snf1 were deleted. The deletion was caused by an intragenic recombination event between two 8-bp direct repeats flanking six intervening codons. In contrast to truncated forms of Snf1 that contain only the kinase domain, the Snf4-independent Snf1Δ311 − 316 was fully functional and could replace wild-type Snf1 for normal growth, because it retained the ability to interact with the Kis1 and Kis2 β-subunits via its C-terminal domain. Indeed, the Snf4-independent Snf1Δ311 − 316 still required the β-subunits of the SNF1 complex to perform its functions and did not rescue the growth defects of kis1Δ mutants. Our results demonstrate that a preprogrammed in-frame deletion event within the SNF1 coding region can generate a mutated form of this essential kinase which abolishes autoinhibition and thereby overcomes growth deficiencies caused by a defect in the γ-subunit Snf4. IMPORTANCE Genomic alterations, including different types of recombination events, facilitate the generation of genetically altered variants and enable the pathogenic yeast Candida albicans to adapt to stressful conditions encountered in its human host. Here, we show that a specific recombination event between two 8-bp direct repeats within the coding sequence of the SNF1 gene results in the deletion of six amino acids between the N-terminal kinase domain and the C-terminal regulatory domain and relieves this essential kinase from autoinhibition. This preprogrammed deletion allowed C. albicans to overcome growth defects caused by the absence of the regulatory subunit Snf4 and represents a built-in mechanism for the generation of a Snf4-independent Snf1 kinase.